PROSPECTS FOR THE DEVELOPMENT OF SERVICE INDUSTRIES - Bekmirzayev, Mirzohid; Xolikov, Javohir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this article, the development of the service industry in the conditions of ensuring economic stability, increasing its importance, the economic analysis of the activity of the service industry today, and the further development of the service network in the future are described in detail. Service sector - part of the economy, which includes all types of commercial and non-commercial services; a consolidated general category that includes the reproduction of various types of services provided by enterprises, organizations, and individuals. It is customary to include culture, education, health care, and consumer services in the service sector. The service sector is often referred to as a post-industrial economic structure due to their well-developed modern infrastructure. It is the service sector that, in economically developed countries, makes up the bulk of the economy in terms of the number of employees. The service sector includes: the service sector (infrastructure services for the production and service sectors of the economy) and the social sector (services for the non-production and legal and financial sectors of the economy).